Community-based case control study on the risk of fall among elderly in Kaniyambadi block, Vellore, Tamil Nadu, India - Alex Joseph; Jayaprakash Muliyil (Elsevier, 2021)
Background: Fall injuries are a major cause of morbidity and disability in elderly. The magnitude of association of risk factors, the economic burden, and other consequences of fall in the elderly is less studied in India. Methods: A Community based matched case-control study was conducted among elderly ≥60 years, elders with a history of fall in the past 1 year was identified as cases. One control per case were selected, each case and control were matched for age and gender. Both groups were randomly selected from older people (age ≥60) living in Kaniyambadi block identified by door-to-door survey. Univariate analysis, stratified analysis and multivariate analysis was performed. Results: Having 141 cases of fall among 776 elders contacted, 18.17% (15.6-21.1) was estimated as the incidence of fall. The independent risk factors were identified as dizziness OR 2 (1.3 to 3.8) times and difficulty in walking OR 3 (1.7 to 5.9) times more likely for fall. Certain risk factors were found to be different in men and women. Among the 141 falls 110 (78%) had economic burden due to fall. Rs. 2370 was the mean expense for a fall, maximum of Rs 33,000 to a minimum of Rs 10 were spent because of falling. Conclusion: This study was one of the first community bases case-control studies in India on the risk of fall in elderly people. The study provides the important information on risk and protective factors for fall in rural Indians. The information could be used to develop targeted interventions to prevent the fall in this vulnerable age group.